Loan Loss Provisioning and Efficiency: A Study of Frontier Market Banks - Martens, Wil; Bui, Chau Ngoc Minh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
This paper investigates frontier market bank managers’ use of the discretionary component of loan loss provisions to manage earnings and its association with efficiency. Studies have documented that bank managers use loan loss provisions to smooth earnings, yet the association of provisioning with efficiency in frontier markets has not been empirically examined. Employing stochastic frontier analysis as a method of efficiency assessments in 22 frontier market countries, results show bank efficiency declined steadily from 2001 to 2018. This finding is contrary to eco nomic efficiency theory and suggests that loan quality difficulties have persisted despite nations enjoying increasing economic development. Regression analysis results further reveal that earnings management (EM) via loan loss pro visioning is inversely related to efficiency. Study findings support prospect theory, indicating that managers engage in risk-seeking behavior while making risk-averse judgments. Overall, the study results imply that banks should expand loan provisioning strategies to optimize resource allocation and business performance.